Characteristics and causes of death in children with neonatal abstinence syndrome. (20th August 2020) - Uebel, Hannah; Wright, Ian M; Burns, Lucinda; Hilder, Lisa; Bajuk, Barbara; Breen, Courtney; Abdel‐Latif, Mohamed E; Falconer, Janet; Clews, Sarah; Ward, Meredith; Eastwood, John; Oei, Ju Lee
Abstract : Aim: To determine characteristics of death in children with neonatal abstinence syndrome (NAS). Methods: A population‐based linkage study of children from birth to 13 years of age in New South Wales (NSW), Australia, born 1 July 2000 to 31 December 2011. Infants with an International Statistical Classification of Diseases and Related Problems, Australian modification coding of NAS (P96.1, n = 3842) were compared to infants ( n = 1 018 421) without NAS by birth, hospitalisation and death records linkage. Results: Forty‐five (1.2%) children with NAS died, compared to 3665 (0.4%) other children. Most deaths ( n = 30, 66%) in NAS children occurred between 1 month and 1 year. Risk of death was independently increased in full‐term children (hazard ratio 2.34, 95% confidence interval 1.63–3.35; P  < 0.001) from lower socio‐economic groups (1.23, 1.12–1.35; P  < 0.001), most commonly from ill‐defined or external causes, including assault and accidents ( P  < 0.001). Conclusions: Children with NAS, especially those of term gestation and from lower socio‐economic groups, are more likely to die, especially from external causes.